2015
DOI: 10.1016/j.ejvs.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Gender related Long-term Differences after Open Infrainguinal Surgery for Critical Limb Ischemia

Abstract: Gender-related disparity in critical limb ischemia open surgical revascularization outcomes still remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Lejay evaluated 269 women and 315 men with critical limb ischemia, showing that female gender was an independent factor predicting death, even with adjustment for age. 19 One result of our investigation was that Brazilian women were associated with a higher in-hospital mortality rate (112/1,000 cases versus 85/1,000 cases; p<0.05) and a higher chance of death (OR=1.36; p<0.05) due to emergency arterial occlusions.…”
Section: Discussionmentioning
confidence: 65%
“…Lejay evaluated 269 women and 315 men with critical limb ischemia, showing that female gender was an independent factor predicting death, even with adjustment for age. 19 One result of our investigation was that Brazilian women were associated with a higher in-hospital mortality rate (112/1,000 cases versus 85/1,000 cases; p<0.05) and a higher chance of death (OR=1.36; p<0.05) due to emergency arterial occlusions.…”
Section: Discussionmentioning
confidence: 65%
“…Our finding of higher odds of acute graft failure in women is in agreement with the non-HD literature. 13,16,17 Despite the higher prevalence of prosthetic grafts and the higher risk of acute graft failure in women compared with men, there were no significant differences in limb loss in the short and long term. This is possibly due to strategies that promote recognition and salvage of failing and failed grafts.…”
Section: Discussionmentioning
confidence: 96%
“…Sex-based disparities have been described in the incidence of PAD, outcomes of infrainguinal bypass surgery in non-HD patients, and non-PAD-related vascular surgery performed in dialysis patients. 2,[10][11][12][13][14] However, a comprehensive delineation of outcomes according to sex in a nationally representative cohort of HD patients that could guide decision-making and risk stratification is lacking. Prior studies have been limited by small sample sizes, single-institutional sources, or absence of detail across categories of gender.…”
mentioning
confidence: 99%
“…Other French colleagues from the University of Strasbourg demonstrated a significantly lower survival rate at 6 years, but not at 30 days, among women compared to men undergoing infra-inguinal open surgery for CLTI. They concluded that female sex was an independent factor predicting death [ 24 ].…”
Section: Discussionmentioning
confidence: 99%